2018
DOI: 10.1038/s41598-018-34557-7
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-Ligand Interaction Mediates Targeting of Endothelial Colony Forming Cell-derived Exosomes to the Kidney after Ischemic Injury

Abstract: Endothelial colony forming cell (ECFC)-derived exosomes protect mice against ischemic kidney injury, via transfer of microRNA-(miR)-486-5p. Mechanisms mediating exosome recruitment to tissues are unclear. We hypothesized that ECFC exosomes target ischemic kidneys, involving interaction between exosomal CXC chemokine receptor type 4 (CXCR4) and stromal cell-derived factor (SDF)-1α. Ischemia-reperfusion was induced in mice by bilateral renal vascular clamp, with intravenous infusion of exosomes at reperfusion. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
61
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 80 publications
(62 citation statements)
references
References 34 publications
1
61
0
Order By: Relevance
“…Since MSCs are known to accumulate in damaged tissues through the interactions of receptors on the MSCs and target tissues [109,110], it is highly probable that MSC-exosomes are also localized in damaged tissues due to these receptor interactions. Similarly, exosomes from endothelial progenitor cells showed accumulation in ischemic kidney to prevent ischemic injury through CXCR4-SDF-1α interaction [91].…”
Section: Accumulation Of Msc-exosomes In Damaged Tissuesmentioning
confidence: 99%
“…Since MSCs are known to accumulate in damaged tissues through the interactions of receptors on the MSCs and target tissues [109,110], it is highly probable that MSC-exosomes are also localized in damaged tissues due to these receptor interactions. Similarly, exosomes from endothelial progenitor cells showed accumulation in ischemic kidney to prevent ischemic injury through CXCR4-SDF-1α interaction [91].…”
Section: Accumulation Of Msc-exosomes In Damaged Tissuesmentioning
confidence: 99%
“…In the brain, in vivo neuroimaging of gold-labeled EVs has shown that EVs home to areas of brain pathologies in mice, but distribute diffusely in uninjured brains [33,34]. One study has shown that human umbilical vein endothelial cell (HUVEC)-derived EVs home to ischemic kidneys, but not uninjured kidneys, for at least 4 h post-injection, an effect likely mediated by CXCR4/SDF-1α interactions [35]. Even less studied are methods to further optimize EV homing to specific target tissues.…”
Section: Discussionmentioning
confidence: 99%
“…Mostly homes to the liver and spleen, and surface engineering of exosomes can induce targeting ability …”
Section: Therapeutic Potential and Manufacturing Of Msc‐derived Evsmentioning
confidence: 99%
“…Similarly, He et al showed protection against kidney damage in the subtotal nephrectomy murine model of renal regeneration by decreasing the levels of uric acid, creathinine, fibrosis, and lymphocyte infiltration by treating MSC-derived EVs [31]. In another murine [29,30] Retains therapeutic effects of MSCs, and loading therapeutic cargo can increase their effects [2,5,25,31,32] Homing to target tissue Home to sites of injury and cancer, but less than 1% of MSCs result in engraftment [33] Mostly homes to the liver and spleen, and surface engineering of exosomes can induce targeting ability [34][35][36] Can pass though the blood-brain barrier [37] Rejection Can induce allogenic immune rejection [38,39] Considered to be nonimmunogenic [41]. Furthermore, the therapeutic potential of MSCderived EVs was also verified in a murine model of fibrotic liver induced by carbon tetrachloride [5] and in a rat skin burn model [42].…”
Section: Exogenous Msc Evs In Tissue Regenerationmentioning
confidence: 99%